Аналіз особливостей волоконно-оптичних сенсорів - Новенко, М. Д. (ХНУРЕ, 2020)
The general analysis of fiber-optic sensors features is carried out in work. These features are considered from aspect of use field; from aspect of operation principle and design features. As a result, analysis made it possible to identify main parameters for which it is planned to develop a structural-parametric model, which will further develop an automated system that will work as a reference and cumulative in order to select required FOS model.
Keywords: автоматизовані системи; волоконно-оптичні сенсори; структурно-параметричні моделі